Changing attitudes in Japan toward HPV vaccination: a 5-year follow-up survey of obstetricians and gynecologists regarding their current opinions about the HPV vaccine - Yoshikazu Nagase; Yutaka Ueda; Hazuki Abe; Asami Yagi; Masaaki Sawada; Satoshi Nakagawa; Kosuke Hiramatsu; Tomomi Egawa-Takata; Shinya Matsuzaki; Eiji Kobayashi; Toshihiro Kimura; Tadashi Kimura (Taylor & Francis Group, 2020)
In Japan, the governmental recommendation for HPV vaccination was suspended in June 2013 because of media reports of so-called adverse vaccine events. The HPV vaccination rate in Japan prior to this suspension was almost 70%, but fell afterward to almost zero. To explore ways to bolster HPV vaccination, between 2014 and 2019 we conducted three serial surveys of the opinions of obstetricians and gynecologists about HPV vaccination. This study aimed to discuss the changing attitudes found in this 5-year follow-up survey. In August 2014, January 2017, and June 2019, we posted questionnaires to about 570 obstetricians and gynecologists practicing in Osaka, Japan. All three surveys used the same structured and closed-ended questionnaire, including questions about their personal opinions regarding HPV vaccination. We compared our new results to those of the previous two surveys. The response rate for the latest survey was 51.1% (293/573), which was equivalent to the previous two surveys. Among the responders, 83.3% (244/293) now thought that the Japanese government should restart its HPV vaccine recommendation, and 84.6% (248/293) were already recommending HPV vaccines for teenagers in their daily care. Eleven of 30 doctors (36.7%) had their own teenage daughters vaccinated against HPV after the suspension of recommendation. The rate has maintained an increasing trend from the previous two surveys. This study indicated that the attitude of obstetricians and gynecologists in Japan toward HPV vaccination has changed positively over 5 years. The results should serve as an encouragement to resume the governmental recommendation of HPV vaccines.